Pengembangan Desain Sistem Suplai Brown's Gas Model 6 Cell Tersusun Seri dan Implementasinya pada Mobil Suzuki Karimun GX 970 CC - Rahman Hakim; Harus L Guntur (JURNAL INTEGRASI, 2013)
Brown's Gas electrolysis system is a water electrolysis system coupled with a catalyst that can produce pure hydrogen and oxygen which have calorific value and high octane. In several studies that have shown that its application to existing vehicles can increase fuel efficiency and increased torque. The resulting gas also contains water vapor to cool the engine and lowering emissions Cox. The result showed the highest increase in power is at 7.83% which is 0.4 Hp at Brown's Gas Type B without Silica Gel / [BG B (-SG)]. Sfc biggest decline 26.45% ie 0.0426 mm Kg / Hp hours on BG B (-SG). Increased levels of HC for BG A (+ SG) of 348.5 ppm, increased levels of CO exist in BG A (+ SG) of 3.06%, an increase in CO2 levels is in BG A (-SG) of 12.47%, λ there is a decrease in BG A (+SG) of 0.54%